2020
DOI: 10.1155/2020/5969326
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge towards Prevention and Early Detection of Chronic Kidney Disease and Associated Factors among Hypertensive Patients at a Chronic Illness Clinic of Jimma Town Public Hospitals

Abstract: Background. Morbidity and mortality due to chronic kidney disease are increasing among hypertensive patients in Sub-Saharan Africa. The majority of hypertensive patients with chronic kidney disease are not diagnosed at an early stage because of poor knowledge. However, to the best of our knowledge, there is no study conducted in Ethiopia about knowledge of hypertensive patients towards prevention and early detection of chronic kidney disease. Thus, the aim of this study was to assess knowledge towards preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In this study, the correct rate of disease knowledge answers in patients with hypertensive nephropathy was 77.8%, showing a medium to high level, which is higher than that in less developed countries, such as 47.9% in Gima, Ethiopia, Africa (Tegegne et al, 2020), 68.7% in Gondar Town, Ethiopia, Africa (Asmelash et al, 2020), 50% in Indonesia (Agustiyowati, 2020), and 26.3% in Malaysia, which is a developed country (Ng et al, 2016). The results of this study are different from those of the above-mentioned scholars, which may be attributed to the promotion of health policies by governments in different countries.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, the correct rate of disease knowledge answers in patients with hypertensive nephropathy was 77.8%, showing a medium to high level, which is higher than that in less developed countries, such as 47.9% in Gima, Ethiopia, Africa (Tegegne et al, 2020), 68.7% in Gondar Town, Ethiopia, Africa (Asmelash et al, 2020), 50% in Indonesia (Agustiyowati, 2020), and 26.3% in Malaysia, which is a developed country (Ng et al, 2016). The results of this study are different from those of the above-mentioned scholars, which may be attributed to the promotion of health policies by governments in different countries.…”
Section: Discussionmentioning
confidence: 55%
“…A study conducted in Jordan revealed that most of the participants had appropriate knowledge about CKD [ 28 ]. Moreover, nearly half of the participants in a study conducted by Tegegne et al were well-knowledgeable on the prevention and early detection of CKD [ 29 ]. Contrary to these findings, in a study of the Australian public’s understanding of CKD, half of the participants had knowledge scores of less than the median [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, 37.5% of hypertensive patients had a good knowledge of chronic kidney disease [16]. In Nigeria, 26.1 [17] and in Ethiopia 47.9 [18]. This difference between countries may be due to differences in study design and tools.…”
Section: Level Of Knowledge Of the Renal Risk Associated With Hyperte...mentioning
confidence: 99%